Penggambaran Bentang Alam dalam Serat Rama dan Kakawin Ramayana - Sadewa, Tio Cahya (Jumantara: Jurnal Manuskrip Nusantara, 2024)
Landscapes are natural scenery or areas with various forms of the earth's surface (mountains, rice fields, valleys, rivers, and so on) which together constitute a single entity. Many depictions of landscapes are recorded in old literary works. One of the Javanese literary works that records the depiction of landscapes is Serat Rama. Serat Rama is a new Javanese literary work composed by R. Ng. Yasadipura in Surakarta which is derived from the Kakawin Ramayana in Old Javanese. Both texts tell the story of Prabu Rama's journey to rescue his wife, Dewi Sinta, who was kidnapped by Prabu Rahwana in Alengka. During his journey, Prabu Rama has passed through various landscapes accompanied by obstacles and obstacles. This paper attempts to answer the problem, namely how is the landscape depicted in Serat Rama and Kakawin Ramayana? By knowing the depiction of landscapes in old literary works, there will be a little picture for today's readers about natural conditions in the past. This paper applies a philological research method with an ecocritical approach. Data collection was done by inventorying the stanzas in Serat Rama and Kakawin Ramayana that describe landscapes to be translated, described, and compared. The depictions of landscapes in Serat Rama and Kakawin Ramayana were sorted into (1) depictions of forests, (2) depictions of mountains, and (3) depictions of waters. The results show that the depiction of landscapes in Kakawin Ramayana appears more detailed and some are still influenced by the Indian natural setting. In Serat Rama, the author tries to depict landscapes by localizing them to suit the Javanese natural setting. There are several names of landscapes that exist in Kakawin Ramayana but are not found in Serat Rama. There are also some differences in mentioning the names of landscapes that arise due to word-cutting errors and different interpretations when recomposing the kakawin.